Mind in the balance : meditation in science, Buddhism, and Christianity - Wallace, B. Alan (Columbia series in science and religion., 2014)
By establishing a dialogue in which the meditative practices of Buddhism and Christianity speak to the theories of modern philosophy and science, B. Alan Wallace reveals the theoretical similarities underlying these disparate disciplines and their unified approach to making sense of the objective world. Wallace begins by exploring the relationship between Christian and Buddhist meditative practices. He outlines a sequence of meditations the reader can undertake, showing that, though Buddhism and Christianity differ in their belief systems, their methods of cognitive inquiry provi.